Women in Working Life and Overview of Studies on This Theme with “Glass Ceiling” Concept - Ebru Çitil (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Although female employment rate in working life is high today, it is unfortunately not possible to see the same rate in managerial staff. Barriers to women's promotion to senior executive positions are based on gender, roles, stereotypes and prejudices, defined as invisible barriers in the glass ceiling concept. The fact that female workforce, has been more involved in working life in recent years necessitates to conduct a study on the concept of glass ceiling. The aim of this study is to examine the concept of "glass ceiling" by considering the theoretical information in this matter and the results of the studies conducted around the world. In this regard, this study aims to reveal can be done in the process of struggling with the glass ceiling, drawing attention to the gender-related stereotypes, prejudices, female workforce abroad and in Turkey, glass ceiling factors leading to these barriers, the measures that can be taken against the barriers and regulations. For this purpose, many studies conducted on this issue in different countries have been examined. These studies have shown that the ‘glass ceiling’ effect makes its presence felt in organizations that are actively present in professional working life all over the world. The results obtained from these studies also reveal that this situation negatively affects the careers of female employees and brings about important problems in their daily working lives.